Characterization and selection of inter simple sequence repeat markers for genetic studies of mesquite - Anjos, Quirlian Queite Araújo (2022)
Since characterization and selection of molecular markers are crucial steps in genetic research for plant conservation and/or (pre) breeding, this study aimed to describe the amplification profile of Inter Simple Sequence Repeat (ISSR) markers in Prosopis juliflora (Sw.) DC. so that the most suitable ones could be selected. To do so, the genomic DNA of 16 individuals collected at the Federal Institute - Campus Itapetinga, Bahia State, were extracted at the Applied Molecular Genetics Laboratory of the State University of Southwest Bahia, in Itapetinga-BA (Brazil). The amplification profile was obtained using 23 ISSR primers, visualized after electrophoresis in 2% agarose gels, and photo-documented under ultraviolet light; then, genotyping was performed. In total, amplification of 206 markers was observed, with an average of nine tags per primer, a polymorphic percentage equivalent to 90% of the markers generated; and mean polymorphic information content of 0.63. Expected and observed heterozygosity means were similar (0.28 and 0.29, respectively). Our findings confirm that ISSR primers are suitable for molecular-genetic studies of P. juliflora. Among the 23 analyzed primers, 13 can be prioritized (DiGA3’G, DiCA 3'RG, DiCA 3'YG, DiGA 3'C, DiGA 3'RC, DiGA 3'T, TriCAG 3'RC, TriTGT 3'YC, TriAAC 3'RC, TriAAG 3'RC, TriCGC 3'RC, TriGAC 3'RC, and TriGGA 3'RC) for genetic studies of P. juliflora.